2006
DOI: 10.1186/1472-6963-6-90
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of qualitative research in designing a complex intervention for secondary prevention of coronary heart disease in two different healthcare systems

Abstract: Background: Developing complex interventions for testing in randomised controlled trials is of increasing importance in healthcare planning. There is a need for careful design of interventions for secondary prevention of coronary heart disease (CHD). It has been suggested that integrating qualitative research in the development of a complex intervention may contribute to optimising its design but there is limited evidence of this in practice. This study aims to examine the contribution of qualitative research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…For example, one of the included studies [10] took place in Ireland and showed that the two different healthcare systems (in Northern Ireland and the Republic of Ireland) did impact on delivery of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one of the included studies [10] took place in Ireland and showed that the two different healthcare systems (in Northern Ireland and the Republic of Ireland) did impact on delivery of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A number of qualitative studies have explored the views and experiences of nurses who have delivered HBC interventions in primary care [9][10][11][12][13][14][15][16][17][18]. The synthesis of such studies can develop understanding of factors that could enhance delivery of and adherence to such interventions.…”
Section: National Institutes Of Health Behavior Change Consortium (Nimentioning
confidence: 99%
See 1 more Smart Citation
“…Such research is challenging since so many factors influence quality of care that even randomized trials can be confounded by informal and potentially uneven diffusion of knowledge. Ideally, a mixed methods approach should be applied to produce information of sufficient detail for decision makers-randomization of the intervention to quantify its impact, coupled with qualitative process evaluations to identify how the intervention achieved its effect [163][164][165].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 It can also facilitate in-depth exploration as well as an understanding of underlying social and contextual issues. 21 The current study aimed to explore the feasibility and acceptability of a social inclusion intervention for improving medication adherence for people with severe mental illness in Cape Town. The proposed intervention will include adherence support for people with mental disorders and their family or elected support networks, collectively to be identified as treatment partners.…”
Section: Introductionmentioning
confidence: 99%